2008
DOI: 10.1002/vnl.20144
|View full text |Cite
|
Sign up to set email alerts
|

Metal hydroxystannates as flame retardants and smoke suppressants for semirigid poly(vinyl chloride)

Abstract: Metal hydroxystannates were studied as flame retardants and smoke suppressants for semirigid poly(vinyl chloride) (PVC). The flame-retardant and smoke-suppression mechanisms were investigated by using limiting oxygen index (LOI), smoke density rating (SDR), the solid yield test (SY), scanning electron microscopy (SEM), thermogravimetry, differential thermogravimetry, and differential thermal analysis. Results showed that semirigid PVC treated with the flame retardants had a higher LOI, and solid yield, but a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Figure 3c shows that the decomposition temperature of MAZSN is lower than that of MA, which is because the decomposition temperature of the ZHS contained in MAZSN is 220°C 19. Between 227 and 350°C, the dehydration reaction of ZHS overlaps with the sublimation reaction of MA, so a distinct endothermic peak appears at 265°C in the DTA curve.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 3c shows that the decomposition temperature of MAZSN is lower than that of MA, which is because the decomposition temperature of the ZHS contained in MAZSN is 220°C 19. Between 227 and 350°C, the dehydration reaction of ZHS overlaps with the sublimation reaction of MA, so a distinct endothermic peak appears at 265°C in the DTA curve.…”
Section: Resultsmentioning
confidence: 97%
“…The HCl released is an effective gas phase flame inhibitor, and PVC molecules are highly crossl-inked to form carbon films, which play the role of heat insulation and oxygen insulation. 32 The process is demonstrated with TiO 2 in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…The TiCl 4 alkylates with another PVC molecule, and it gives off HCl so as to cause an autocatalytic reaction. The HCl released is an effective gas phase flame inhibitor, and PVC molecules are highly crossl-inked to form carbon films, which play the role of heat insulation and oxygen insulation . The process is demonstrated with TiO 2 in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Then a series of metal hydroxystannates including Mg, Sr, Cu, Co, Ni, Mn, Fe and Zn were added into PVC to compare the flame retardant efficiency by Xu et al . [ 52 ] Among these flame retardants, 2 phr Fe 2 Sn 3 (OH) 18 ‐treated PVC composite showed the highest LOI value as 37.5%, while LOI value of PVC containing 2 phr SrSn(OH) 6 was the lowest as 33.0%. The same research group also combined ZHS with other metal hydroxystannates (metal = Mg, Sr, Mn, Fe, Co, Ni and Cu) and found that ZHS+Fe 2 Sn 3 (OH) 18 showed the best performance.…”
Section: Metal‐based Flame Retardants For Pvcmentioning
confidence: 99%